Modelling of foliage effects for radio military application in tropical forest - Mohamed Ibrahim, Mohamad Anwar; Badron, Khairayu; Hambali, Hasniza; Baktiar, Nor Irza (Collegium Basilea, 2024)
In recent years, military radio is used for the military communication system in the tropical forest. This military radio is using Very High Frequency (VHF) spectrum which the frequency range is from 30 MHz to 300 MHz and also Ultra High Frequency (UHF) spectrum which the frequency range is from 300 MHz to 3 GHz. This research will be focuses on the vegetation effects that influence the signal strength and signal loss of the radio in the forest and to overcome the problem of radio’s signal strength that faced by most of the military. The measurements was conducted in the tropical forest in Malaysia. First of all, simulation of the measurement setup was calculated using a special military HTZ software. Then the measurement was setup and the signal strength was measured from the various distance at foliage area. Then the data was collected and analyzed before proposing a new vegetation model regarding radio military application system in VHF and UHF spectrum. There are three objectives of this research. The first one is to study the communication propagation effects for VHF an UHF bands in tropical forest. The second one is to measure the value of vegetation or foliage loss at tropical forest for VHF and UHF radio and lastly is to develop a model for foliage effect in VHF and UHF frequency. The result of this analysis is very important to the military since this project are collaborating with Science Technology Research Institute for Defense (STRIDE). Besides, other researcher who are doing the same research that meet the condition of this research also can benefit the vegetation model proposed later in this project.